2020
DOI: 10.1159/000509034
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and Adherence to Cationic 0.1% Cyclosporine in Ocular Graft-versus-Host Disease

Abstract: Introduction: Anti-inflammatory, topical therapy of severe keratitis in dry eye disease (DED) and ocular graft-versus-host disease (oGvHD) includes steroids, cyclosporine (Cs), and others. In Germany, a commercial product containing 0.1% Cs in a cationic formulation is available since 2015. Objective: The aim of this study was to present real-life data using cationic 0.1% Cs in oGvHD patients. Methods: This was a retrospective study of 26 oGvHD and 41 DED patients with corneal staining of at least Oxford grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Eye pain and irritation were the most frequently reported treatment-related AEs in the current study, and this is also true for previously published randomized trials [ 20 24 , 27 ]. While previous studies highlight that some populations may experience tolerability issues (particularly discomfort/pain at the site of instillation), just 31 participants (6.6% of the FAS) withdrew from the PERSPECTIVE study due to poor local tolerance, which was also slightly lower than the proportion withdrawing due to ocular treatment-related AEs in the SANISKA/SICCANOVE pooled analysis (9.3%) [ 20 , 32 34 ].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Eye pain and irritation were the most frequently reported treatment-related AEs in the current study, and this is also true for previously published randomized trials [ 20 24 , 27 ]. While previous studies highlight that some populations may experience tolerability issues (particularly discomfort/pain at the site of instillation), just 31 participants (6.6% of the FAS) withdrew from the PERSPECTIVE study due to poor local tolerance, which was also slightly lower than the proportion withdrawing due to ocular treatment-related AEs in the SANISKA/SICCANOVE pooled analysis (9.3%) [ 20 , 32 34 ].…”
Section: Discussionmentioning
confidence: 91%
“…This resulted in the inclusion of a heterogenous study population, which is reflective of routine clinical practice but may present challenges when comparing treatment outcomes against those from randomized trials examining CsA 0.1% CE use in a homogenous and stringently selected group [ 21 24 ]. Nonetheless, as demonstrated in previously published retrospective and observational analyses, real-world studies enable factors such as treatment tolerance to be examined at a practical level to improve understanding regarding those patients who may be best suited to CsA 0.1% CE therapy as well as those who would benefit from a different approach [ 25 , 32 , 34 ]. In accordance with usual clinical practice in the real-world setting, patients were allowed to continue AT therapy throughout the study, which could have contributed to the healing of the corneal surface and the therapeutic effect observed with CsA 0.1% CE treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, cationic 0.1% CSA is considerably less tolerated. Common intolerable symptoms include burning sensations, redness, conjunctival and lid swelling, and itching ( 94 ). Tacrolimus, with a mechanism of action similar to that of cyclosporine, is more effective than CSA ( 95 ).…”
Section: Pathogenic Mechanism and Novel Therapeutic Targetsmentioning
confidence: 99%
“…Most commonly used symptom parameters 41,42,[55][56][57][58][59][60][61][62]74,82,88,89,92 Least commonly used symptom parameters 41,42,55,56,58,62,88,89 Most commonly used sign parameters 41,42,[55][56][57][58][59][60][61][62][63][64]72,74,82,88,89,92 Least commonly used sign parameters 41,42,[55][56][57][58]62,89 Although studies have shown that the majority of patients and physicians (60-80%) are satisfied overall with topical CsA in DED, 95,…”
Section: Patient Educationmentioning
confidence: 99%